TATBIQ TORIQOH AL QAWAID WA TARJAMAH FI TANMIYATI MAHARATUL KITABAH - Asro, Dwi Nuzilatul; Rohman, Fathur (El-Tsaqafah : Jurnal Jurusan PBA, 2023)
This research aims to explain Arabic language learning using grammar and translation methods that can train students in writing, measure students' memory, increase Arabic vocabulary, facilitate the translation process, make it easier to determine the position of sentences and compose essays, as well as train other writing skills. This research was conducted at MAN 2 Jombang with the aim of knowing about writing skill learning, applying the grammar and trasnlation method to increase skill, and knowing the supporting and inhibiting factors of applying the method. This study uses a qualitative approach method, namely by using a descriptive qualitative research method. Data was collected using observation, interview, and documentation methods. The collected data in the form of words were analyzed by means of data reduction, data presentation, and drawing conclusions. The results of this study indicate that (1) the ability to memorize books of class XI students at MAN 2 Jombang is quite good as seen from learning Arabic at each meeting. (2) the application of the grammar and trasnlation method is to make it easier for students to improve writing skill. (3) The advantages of implementing this are that it makes it easier for students to determine the position of sentences by understanding the nahwu shorof rules and also makes it easier for students to translate from Arabic to Indonesian and vice versa. While the drawback of this method is the quick explanation of the material by the teacher in a short time.